THE ANALYSIS OF A SMALL-AMPLITUDE STRUCTURE FOR COSMIC OBJECTS LIGHT CURVES - Korobko, A. A.; Dobrovolsky, A. V.; Shumilov, Yu. P.; Paltsev, N. G.; Chaichuk, R. A.; Strakhova, S. L. (Одеські астрономічні публікації, 2017)
In the given work a small-amplitude structure for stabilized cosmic objects (CO) light curves is considered by an example of orbital complex ”Salyut-7” light curves in various versions of the ”bundle”. Coefficients s and s: are determined of noise and determined” components the velocity of ratio variation of which i may serve as a sign of undocking (docking) of the objects at their optical unresolvability.